Modeling and vibration analysis of sectional-laminated cylindrical thin shells with arbitrary boundary conditions. (May 2020) - Zhong, Bingfu; Li, Chaofeng; Li, Peiyong
Abstract: The continuity condition is proposed for modeling and analyzing the vibration characteristics of sectional-laminated cylindrical thin shells with arbitrary boundary conditions. The orthogonal polynomials are used to describe the vibration displacements of the sectional-laminated cylindrical shell. Four sets of springs are applied to simulate arbitrary boundary conditions. The Donnell thin shell theory is employed to formulate the theoretical model. To test the convergence and accuracy of the present modeling method, free vibrations of sectional-laminated cylindrical shells are examined with clamped-clamped and simply-simply boundary conditions. The numerical results are compared with those obtained by using the finite element software ANSYS. The effects of the pre-assigned weighted parameters, the length ratio of the non-laminated cylindrical shell and the thickness ratio of inner and outer layers on natural frequencies and mode shapes are presented with arbitrary boundary conditions.